A Design Approach for Controlled Self-Organization-Based Sensor Networks Focused on Control Timescale. (16th May 2013) - Kominami, Daichi; Murata, Masayuki
Many researches on network control with a design principle of self-organization have been studied for large-scale networks. Since self-organized control is based on local interactions between system elements, it has high scalability, adaptability, and robustness; however, the management of the whole system is very difficult. In order to solve this problem, a controlled self-organization scheme has been proposed, which aims for desired system behavior by controlling a part of self-organized nodes. Although there are many practical proposals on the scheme, no design approach for it has ever been investigated. In this paper, we propose and evaluate a design approach for the network based on controlled self-organization, paying attention to the control timescale. Through computer simulations, we show the adaptability and stability of the proposed design approach.